2021
DOI: 10.3390/antibiotics10070855
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nitro-Heteroaromatic Antimicrobial Agents for the Control and Eradication of Biofilm-Forming Bacteria

Abstract: The synthesis and biological activity of several novel nitrothiazole, nitrobenzothiazole, and nitrofuran containing antimicrobial agents for the eradication of biofilm-forming Gram-negative and Gram-positive pathogens is described. Nitazoxanide (NTZ), nitrofurantoin, and furazolidone are commercial antimicrobials which were used as models to show how structural modification improved activity toward planktonic bacteria via minimum inhibitory concentration (MIC) assays and biofilms via minimum biofilm eradicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Those that did not include relevant DMSO controls ( n = 38 articles) often used low concentrations (≤1% DMSO) to deliver treatments, which likely contributed to a reduced perceived need for a solvent control [ 47 , [51] , [52] , [53] , [54] , [55] ]. Studies that used higher DMSO concentrations without solvent controls were more concerning [ 49 , 50 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] as were studies that did not provide concentrations of DMSO used in treatments and did not include solvent controls [ 43 , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. Media-only control-treated biofilms were frequently used in the calculations [ 50 , 56 , 57 , 78 , 79 ] although it is most appropriate to compare treatments delivered with DMSO to DMSO-only control-treated biofilms normalised to 100% growth as in [ 41 , [80] , [81] , [82] ].…”
Section: Resultsmentioning
confidence: 99%
“…Those that did not include relevant DMSO controls ( n = 38 articles) often used low concentrations (≤1% DMSO) to deliver treatments, which likely contributed to a reduced perceived need for a solvent control [ 47 , [51] , [52] , [53] , [54] , [55] ]. Studies that used higher DMSO concentrations without solvent controls were more concerning [ 49 , 50 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] as were studies that did not provide concentrations of DMSO used in treatments and did not include solvent controls [ 43 , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. Media-only control-treated biofilms were frequently used in the calculations [ 50 , 56 , 57 , 78 , 79 ] although it is most appropriate to compare treatments delivered with DMSO to DMSO-only control-treated biofilms normalised to 100% growth as in [ 41 , [80] , [81] , [82] ].…”
Section: Resultsmentioning
confidence: 99%
“…In more recent years, ANT-based motifs have found applications in antibiofilm research, showing promising activity against Escherichia coli, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Clostridium difficile. 2 3 4 5 Previously, most of the reported ANT-based amides were prepared via coupling of 2 with acyl chlorides in the presence of auxiliary bases. Standard procedures using ANT with Et 3 N or K 2 CO 3 as bases involve aqueous workups, which are capricious in that emulsions are often encountered, leading to variable yields (vide infra).…”
Section: Table 1 Yields Of Coupling Reactions Using N-(...mentioning
confidence: 99%
“…Standard procedures using ANT with Et 3 N or K 2 CO 3 as bases involve aqueous workups, which are capricious in that emulsions are often encountered, leading to variable yields (vide infra). 4 6 Subsequent purifications are also tedious, often requiring cautious column chromatography to obtain purified products. Since ANT derivatives have shown significant medicinal promise, an improved synthetic protocol for their synthesis was required.…”
Section: Table 1 Yields Of Coupling Reactions Using N-(...mentioning
confidence: 99%
“…Novel nitro-heteroaromatic compounds synthesized by Koenig et al (2021) showed enhanced antimicrobial activity against Staphylococcus epidermidis and Pseudomonas aeruginosa biofilms [ 4 ]. This study modified the structures of commercial antimicrobials Nitazoxanide, nitrofurantoin, and furazolidone.…”
mentioning
confidence: 99%
“…Additionally, with analogue 7b (2-Amido-5-chloro-N-(5-nitrothizol-2-yl) benzamide), the 2-acetoxy substituent in 1b was replaced with the primary amine group (analog 7b). Both these analogues (1b and 7b) boosted antibacterial activity in the planktonic and biofilm stages [ 4 ].…”
mentioning
confidence: 99%